Axiological Concepts of Islamic Education in Forming Students' Character - M. Hasyim Asyari; Salsabila Putri; Nadhira Shava Putri Ramadhan; Dzakiyatul Fuada; Muhammad Yusron Maulana El Yunusi (Journal Analytica Islamica, 2023)
This research also aims to deepen the value and benefits of character education for young people in Indonesia. The method used is library research or library research, which involves searching and analyzing data from various relevant sources such as books, articles, notes and research reports. Axiology is a branch of philosophy that studies the various ways in which something can be good or bad or have positive or negative consequences in light of one's values and the attendant facts about another's objective existence. Character education is a very important factor in forming personality. It can be said that character education in the context of education in Indonesia is basically the cultivation of educational values, especially noble values which are the culture of Indonesian society and are always well maintained, because the Indonesian nation is a nation famous for its culture.Penelitian ini juga bertujuan untuk memperdalam nilai dan manfaat pendidikan karakter bagi kaum muda remaja di Indonesia. Metode yang digunakan adalah penelitian pustaka atau penelitian kepustakaan, yang melibatkan pencarian dan analisis data dari berbagai sumber relevan seperti buku, artikel, catatan, dan laporan penelitian. Aksiologi adalah cabang filsafat yang mempelajari berbagai cara di mana sesuatu bisa menjadi baik atau buruk atau mempunyai akibat positif atau negatif sehubungan dengan nilai-nilai seseorang dan fakta-fakta yang menyertainya tentang keberadaan obyektif pihak lain. Pendidikan karakter merupakan faktor yang sangat penting dalam membentuk kepribadian. Dapat dikatakan bahwa pendidikan karakter dalam konteks pendidikan di Indonesia pada dasarnya adalah penanaman nilai-nilai pendidikan, khususnya nilai-nilai luhur yang menjadi budaya masyarakat Indonesia dan selalu terpelihara dengan baik, karena bangsa Indonesia adalah bangsa yang terkenal untuk budayanya.